2010
DOI: 10.4103/0971-6203.58780
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of a multi-leaf collimator design for telecobalt machine using BEAMnrc code

Abstract: This investigation aims to design a practical multi-leaf collimator (MLC) system for the cobalt teletherapy machine and check its radiation properties using the Monte Carlo (MC) method. The cobalt machine was modeled using the BEAMnrc Omega-Beam MC system, which could be freely downloaded from the website of the National Research Council (NRC), Canada. Comparison with standard depth dose data tables and the theoretically modeled beam showed good agreement within 2%. An MLC design with low melting point alloy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…20 Most of the MLC designs, available for linacs, use tongue-and-groove arrangements to assemble the leaves in order to reduce the interleaf leakage. The design of the proposed MLC by Singh et al 11 and Ayyangar et al 12 for telecobalt units also uses a similar concept for assembling the leaves. The effect of underdosing in the region of overlap between two adjacent leaves (which is also called as tongue and groove effect) (Ref.…”
Section: Iic Basic Design Of the Mlcmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Most of the MLC designs, available for linacs, use tongue-and-groove arrangements to assemble the leaves in order to reduce the interleaf leakage. The design of the proposed MLC by Singh et al 11 and Ayyangar et al 12 for telecobalt units also uses a similar concept for assembling the leaves. The effect of underdosing in the region of overlap between two adjacent leaves (which is also called as tongue and groove effect) (Ref.…”
Section: Iic Basic Design Of the Mlcmentioning
confidence: 99%
“…To optimize the value of h, an arbitrary value of R = 9.5 cm was chosen as suggested by Ayyangar et al 12 The beam profiles for 10 × 10 cm 2 were generated through the Monte Carlo simulation by varying the values of h in the range of 0-7 cm (the leaf height of proposed MLC = 7 cm and hence the maximum value of h = 7 cm). The value of h which produced a radiation field width closer to nominal field width was selected as its optimum value.…”
Section: Iic3 Leaf End Shapementioning
confidence: 99%
See 1 more Smart Citation
“…In a previous publication,[ 1 ] the Monte Carlo (MC) modeling of the cobalt machine using the approach published by Mora et al .,[ 2 ] in 1999 was presented. In that paper,[ 1 ] the cobalt source and the collimator systems were modeled using BEAMnrc software and showed that the central axis PDD matched with published values from British Journal of Radiology Supplement 25 (BJR25). The beam profiles for a 10 × 10 cm 2 field were presented; however, they were not compared with any realistic profile data.…”
Section: Introductionmentioning
confidence: 99%
“…The model was used to test the MLC leakage using 6-cm tungsten leaves at a source distance of 48 cm. That paper[ 1 ] also presented the use of low melting point alloy (LMPA) and concluded that tungsten is preferable for the construction of the MLC leaves. The methodology of the current MC simulation follows the same approach as previously published.…”
Section: Introductionmentioning
confidence: 99%